2018
DOI: 10.7250/bjrbe.2018-13.412
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Hazard Assessment of RC Bridges using Unmanned Aerial Vehicle-Based Measurements

Abstract: The structural performance of reinforced concrete bridges is crucial regarding the bridge safety. Monitoring the bridge performance under multihazard effects such as scour, and earthquake becomes even more important. Thus, the scour depth along the piers and piles of bridge substructures has to be measured and tracked consistently in order for reliable multi-hazard bridge behaviour predictions. A practical Unmanned Aerial Vehicle based scour measurement method was proposed to increase the measurement accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This technique is shown as reliable and efficient for collecting surface data for streams and rivers (Micheletti et al, 2015). For river bathymetry modeling, the bathymetric data acquired from high-resolution UAV-derived images at shallow water were verified with real data and high correlation was obtained (Flener, 2013;Ozcan & Ozcan, 2018, 2019.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This technique is shown as reliable and efficient for collecting surface data for streams and rivers (Micheletti et al, 2015). For river bathymetry modeling, the bathymetric data acquired from high-resolution UAV-derived images at shallow water were verified with real data and high correlation was obtained (Flener, 2013;Ozcan & Ozcan, 2018, 2019.…”
Section: Introductionmentioning
confidence: 92%
“…Since the UAV based measurement methods procure data at extremely high spatial resolution (centimeter scale), the measurement precision is comparable to traditional surveying techniques (Carrera-Hernández et al, 2020). The direct applications of UAV-based measurement methods related to elevation, aspect, and stream distribution was useful in surface investigations and in analyzing hydrologic response by means of river mapping and floodplain characterization (Rusnák et al, 2018), riverbank and floodplain surveying (Tamminga et al, 2015), scour monitoring in bridges (Ozcan & Ozcan, 2018;Ozcan & Ozcan, 2019), and DEM generation over various scales and landscapes (Gafurov, 2018). UAVbased measurements provide a data collection platform between the point (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Another emerging imaging-based application with UAVs is the displacement/deformation measurement techniques of bridge structure, e.g., photogrammetric computer vision [9], [83], [89], [97], [146] and digital image correlation (DIC) [79], [92]- [95], [148]. Despite these imaging-based techniques, it is also worth mentioning the use of Laser Doppler Vibrometers (LDV) in UAVs as a non-contact sensor to measure bridge displacements [84]- [86].…”
Section: Concretementioning
confidence: 99%
“…In recent years, fine topographic changes were examined by using orthomosaics and digital surface models (DSMs) which could be produced by remote sensing methods instead of classical terrestrial measurement techniques. In this context, the use of UAVs in conjunction with low-cost, user-friendly Structure from Motion (SfM) photogrammetric technique are highly suitable to produce high-resolution orthomosaics and DSMs depending on UAV flight altitudes and mounted camera systems [10][11][12][13]. Comparative studies considered in different geomorphic regions have shown that the accuracy of high-resolution topographic data derived from SfM is similar to those produced by traditional methods [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%